FACTORS IMPACTING ON SUCCESSFUL WARFARIN REVERSAL WITH THREE FACTOR PROTHROMBIN COMPLEX CONCENTRATE (3F-PCC) – A SINGLE CENTRE EXPERIENCE. (February 2015) - Lukito, Pohan; Dauer, Ray; Haberfield, April; Morgan, Susan; Tran, Huyen
Abstract : Aim: A recent Australian warfarin reversal guideline recommended dosing 3F-PCC according to patients' pre-INR. Our study examines factors impacting on warfarin reversal, including pre-INR, 3F-PCC dose and use of vitamin-K and FFP. Methods: A retrospective analysis was conducted on 88 patients receiving 3F-PCC between June to October 2014. Successful warfarin reversal is defined as post-treatment INR < 1.5. Chi-square and Mann-Whitney tests were used to compare differences between groups. Results: 87 of 88 patients received 3F-PCC for warfarin reversal; 53% for bleeding and 42% prior to urgent surgery. Median time to post-INR was 3 hours. Seventy-six percent of patients achieved post-INR < 1.5 with median pre-INR of 2.5 (1.5–20) and median 3F-PCC dose of 34 (7–65) IU/kg; 23% of these patients also received FFP. In the patients who had post-INR ≥ 1.5 (24%), no statistically significant differences were observed in median pre-INR [2.9 (1.9–17.3), p = 0.1], 3F-PCC dose [25 (13–67) IU/kg, p = 0.07] and proportion of patient who received FFP (31%, p = 0.47) compared to those with INR < 1.5. Most patients received vitamin K in both groups. Conclusion: In 3F-PCC use for warfarin reversal, pre-INR, 3F-PCC dose and FFP do not appear to significantly impact post-INR correction. Larger studies are required to explore the feasibility of a fixed 3F-PCC dose to simplify the current guideline.